METHODOLOGY FOR DEVELOPING COMMUNICATIVE COMPETENCE OF CADETS WHEN THEY ARE ORIENTED TO THE PROFESSION (Web of Technology: Multidimensional Research Journal, 2024)
This article delves into a comprehensive methodology aimed at developing communicative competence among cadets, specifically when they are oriented towards their chosen professions. Communication skills play a crucial role in the success of individuals in any profession, and in the context of military cadets, effective communication is paramount. Through a literature analysis and an exploration of various training methods, this article provides insights into enhancing the communicative competence of cadets in a professional setting. The study also presents results, discussions, and concludes with recommendations for optimizing communicative skills training in military academies.